Bidding decision in land auction using prospect theory - Peng, Yanyan; Liu, Xinwang (International Journal of Strategic Property Management, 2015)
Land auction is widely practiced in company and government decisions, especially in China. Bidders are always faced with two or more auctions in the period of a decision cycle. The outcome of the auction is under high risk. The bidder's risk attitude and preference will have a great influence on his/her bidding price. Prospect theory is currently the main descriptive theory of decision under risk. In this paper, we will consider the preferences of the decision-makers in land bidding decisions with the multi-attribute additive utility and reference point method in cumulative prospect theory. Three land auction models are proposed based on the appearance time of the land auctions. The simultaneous model uses cumulative prospect theory without considering the relationships between the auctions. The time sequential model involves the exchange auction decisions at different time with the third-generation prospect theory. The event sequential model further considers the reference point prediction in sequential land auction decisions. The three models can help the decision-makers make better bidding price decision when they are faced with several land auctions in the period of a decision cycle. A case study illustrates the processes and results of our approaches.First Publish Online: 19 Jun 2015